2019
DOI: 10.1186/s12968-019-0579-7
|View full text |Cite
|
Sign up to set email alerts
|

Free breathing three-dimensional cardiac quantitative susceptibility mapping for differential cardiac chamber blood oxygenation – initial validation in patients with cardiovascular disease inclusive of direct comparison to invasive catheterization

Abstract: BackgroundDifferential blood oxygenation between left (LV) and right ventricles (RV; ΔSaO2) is a key index of cardiac performance; LV dysfunction yields increased RV blood pool deoxygenation. Deoxyhemoglobin increases blood magnetic susceptibility, which can be measured using an emerging cardiovascular magnetic resonance (CMR) technique, Quantitative Susceptibility Mapping (QSM) – a concept previously demonstrated in healthy subjects using a breath-hold 2D imaging approach (2DBHQSM). This study tested utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…To mitigate this issue, we minimized the breath-hold time for each slice (<20 s) to limit cardiac and respiratory motion across the cardiac slice direction. Free-breathing cardiac-gated GRE acquisitions using respiration gating may have the potential to further improve image quality 49 .…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this issue, we minimized the breath-hold time for each slice (<20 s) to limit cardiac and respiratory motion across the cardiac slice direction. Free-breathing cardiac-gated GRE acquisitions using respiration gating may have the potential to further improve image quality 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In brain QSM, M c is typically chosen as the regions containing cerebrospinal fluid. 64 Note that Equation (6) does not model errors from other sources of error, such as when using parallel acquisitions. Using a proper noise weighting in nTFI can help to mitigate this model error (as well as fitting errors from Equation [5]) by assigning small values to w in the problematic voxels, and therefore reducing the influence of these problematic voxels during the optimization.…”
Section: Theorymentioning
confidence: 99%
“…The magnetic fields generated by the magnetized susceptibility sources, henceforth termed the magnetization field, can then be measured by the scanner for susceptibility map reconstruction. Accordingly, QSM can be used to study tissue susceptibility sources such as deoxyheme iron in blood, [6][7][8][9][10][11][12] tissue nonheme iron, [13][14][15][16] myelin, 17 cartilage, 18,19 and calcification. [20][21][22] QSM robustness and reproducibility have been shown for brain applications, 23,24 and there are a wide range of QSM clinical applications, including deep brain stimulation target mapping, 25,26 cerebral cavernous malformation monitoring, [27][28][29] multiple sclerosis chronic inflammation imaging [30][31][32] and MRI follow-up without gadolinium, 31,33 neurodegeneration in Parkinson's disease [34][35][36][37] and Alzheimer's disease, 35,38,39 and more.…”
Section: Introductionmentioning
confidence: 99%
“…phase) distribution [2][3][4][5][6][7][8]. A multitude of clinical and preclinical studies illustrated how QSM can be applied in vivo; for example, to detect vascular abnormalities, visualize blood products and calcifications; microstructural changes and lesions, or map abnormalities in iron metabolism [9][10][11][12][13][14]. These studies have collectively demonstrated that pathological alterations in the brain, heart, muscle and abdomen in various diseases are associated with changes of tissue magnetic susceptibility.…”
Section: Introductionmentioning
confidence: 99%